3-D Joint Inversion of DC Resistivity and Time-Domain Induced Polarization With Structural Constraints in Undulating Topography - Yang, Hetian; Li, Tonglin; Zhang, Rongzhe; Dong, Xintong; Zhuang, Yan (IEEE transactions on geoscience and remote sensing, 2023)
Addressing the significant impact of undulating terrain on 3-D direct current (dc) inversion, the unreliability of traditional linearized polarizability inversion for highly polarizable anomalies, and the nonuniqueness of separate resistivity and time-domain-induced polarization (TDIP) inversion, this article conducts a joint inversion study of 3-D dc resistivity and TDIP with structural constraints in undulating topography. A regularly arranged deformed hexahedron mesh simulates undulating surface terrain, transformed into regular hexahedron elements for 3-D undulating terrain dc resistivity modeling. Based on the exact inversion of polarization calculated from the inversion results of apparent resistivity and equivalent apparent resistivity data, a joint inversion of resistivity and polarization constrained by cross-gradient is implemented. Synthetic data examples show that the application of arbitrary hexahedron elements significantly reduces the influence of terrain on inversion, and the implementation of joint inversion markedly improves the recovery of high-polarization anomalies while enhancing both the model resolution and the inversion accuracy. The proposed algorithm is applied to the joint inversion of resistivity and polarizability in the lead-zinc mining area of Xiagalaiaoyi River in Huzhong area, the Great Khingan Mountains, and Northwestern Heilongjiang Province, achieving good results.